The Effects of a Delayed Incentive on Response Rates, Response Mode, Data Quality, and Sample Bias in a Nationally Representative Mixed Mode Study. Issue 3 (August 2017) - McGonagle, Katherine A.; Freedman, Vicki A.
This article describes the results of an experiment designed to examine the impact of the use and amount of delayed unconditional incentives in a mixed mode (push to web) supplement on response rates, response mode, data quality, and sample bias. The supplement was administered to individuals who participate in the U.S. Panel Study of Income Dynamics, the longest running national household panel in the world. After 10 weeks of data collection, individuals who had not yet completed the interview were sent a final survey request and randomly assigned to one of three treatment conditions: no incentive, US$5, and US$10. The impact of the incentives on response rates and mode, effects on data quality, and sample bias are described. The implications for the use of incentives in mixed mode surveys and directions for future research are discussed.